2022
DOI: 10.3389/fpubh.2022.650719
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to care and treatment among men with reactive HIV self-tests after workplace-based testing in Uganda: A qualitative study

Abstract: IntroductionHIV self-testing at workplaces has the potential to reach men at risk of HIV infection with lower access to HIV testing services. While several studies have reported high uptake of HIV self-testing, linkage to HIV care following a positive result remains a challenge. This study, therefore, explored the motivators for and barriers to linkage to HIV care and treatment among men who returned positive results following workplace-based HIV self-testing.MethodsA qualitative descriptive study, among men i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Our ndings are consistent with earlier studies that reported high to moderate linkage to care in HIVST among men [10,11,13,[44][45][46]. However, in other perspectives, researchers have suggested that there may not be a single best approach to boosting men's utilization of HIV linkage services but rather use of combination strategies including home-based ART initiation, use of phone reminders, and communitybased ART initiation [15,42,43,47]. Fluctuations in linkage under HIVST have been attributed to several facilitators including communication modalities, navigating of health facility systems and processes, linkage-and psychosocial support, which may be countered by innumerable barriers such as in exible work schedules, distance to accessing ART, work transfers, denial of HIV-positive results, and fear of stigma and discrimination at health facilities [15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our ndings are consistent with earlier studies that reported high to moderate linkage to care in HIVST among men [10,11,13,[44][45][46]. However, in other perspectives, researchers have suggested that there may not be a single best approach to boosting men's utilization of HIV linkage services but rather use of combination strategies including home-based ART initiation, use of phone reminders, and communitybased ART initiation [15,42,43,47]. Fluctuations in linkage under HIVST have been attributed to several facilitators including communication modalities, navigating of health facility systems and processes, linkage-and psychosocial support, which may be countered by innumerable barriers such as in exible work schedules, distance to accessing ART, work transfers, denial of HIV-positive results, and fear of stigma and discrimination at health facilities [15].…”
Section: Discussionsupporting
confidence: 91%
“…However, in other perspectives, researchers have suggested that there may not be a single best approach to boosting men's utilization of HIV linkage services but rather use of combination strategies including home-based ART initiation, use of phone reminders, and communitybased ART initiation [15,42,43,47]. Fluctuations in linkage under HIVST have been attributed to several facilitators including communication modalities, navigating of health facility systems and processes, linkage-and psychosocial support, which may be countered by innumerable barriers such as in exible work schedules, distance to accessing ART, work transfers, denial of HIV-positive results, and fear of stigma and discrimination at health facilities [15]. However, VHTs played a vital role in delivering and facilitating oral HIVST, and through the community-based model can continue to conveniently sensitize and guide communities about HIVST, con rmatory testing and other linkage services such as condom use, ART-initiation and re lls, which they may be routinely supporting in their respective communities [44,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that it is crucial to further explore stigma-related concerns to determine how to increase testing among men. HIVST among men plays a pivotal role in promoting access to testing, reducing stigma, and ultimately enhancing the overall health outcomes of specific groups affected by HIV [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…As with other RDTs( 16 ) ( 17 ), patients who self-test do not always report their results or promptly seek care. This is also the case for professionally-tested patients with mild disease whose clinical status deteriorates.…”
Section: Discussionmentioning
confidence: 99%